The role of WRKY transcription factors in exogenous potassium (K+) response to NaCl stress in Tamarix ramosissima - Chen, Yahui; Zhang, Xuanyi; Fan, Yunlong; Sui, Dezong; Jiang, Jiang; Wang, Lei (Frontiers in Genetics, 2023)
Soil salinization poses a significant challenge to plant growth and vitality. Plants like Tamarix ramosissima Ledeb (T. ramosissima), which are halophytes, are often integrated into planting schemes tailored for saline environments. Yet, the role of WRKY transcription factors in T. ramosissima, especially under sodium chloride (NaCl) stress mitigated by exogenous K + application, is not well-understood. This research endeavors to bridge this knowledge gap. Using Pfam protein domain prediction and physicochemical property analysis, we delved into the WRKY genes in T. ramosissima roots that are implicated in counteracting NaCl stress when aided by exogenous K + applications. By observing shifts in the expression levels of WRKY genes annotated to the KEGG pathway under NaCl stress at 0h, 48h, and 168h, we were able to identify potential key WRKY genes.We found that the expression of 56 WRKY genes in T. ramosissima roots responded to exogenous K + application during NaCl stress at the indicated time points. Particularly, the expression levels of these genes were primarily upregulated within 168 hours. From these, 10 WRKY genes were found to be relevant in the KEGG pathways. Moreover, six genes, namely Unigene0024962, Unigene0024963, Unigene0010090, Unigene0007135, Unigene0070215, and Unigene0077293, were annotated to the Plant-pathogen interaction pathway or the MAPK signaling pathway in plants. These genes exhibited dynamic expression regulation at 48 hours with the application of exogenous K + under NaCl stress, suggesting an active role in resisting salt stress. In summary, our research highlights that WRKY transcription factors can modulate the activation or inhibition of related genes during NaCl stress with the application of exogenous K + . This regulation enhances the plant's adaptability to saline environments and mitigates the damage induced by NaCl. These findings provide valuable gene resources for future salt-tolerant Tamarix breeding and expand our understanding of the molecular mechanisms of WRKY transcription factors in alleviating NaCl toxicity.